Uji Toksisitas Akut LC50 Limbah Cair Industri Karet PT. X Terhadap Daphnia Magna Dengan Metode Batch - Suci Pramadita (Jurnal Teknologi Lingkungan Lahan Basah, 2021)
Indonesia is the second largest rubber producer in the world. In rubber production, it produces wastewater that has organic content as well as several high pollutant parameters. Along with the increase in rubber production, the wastewater that will be produced also increases. Wastewater that has a high organic content when directly discharged into water bodies can have a negative impact on the environment and the ecosystem in it. To determine the potential negative impact on the environment and biota, a toxicity test can be used. Acute toxicity test is used to determine the toxicity of rubber wastewater whether it contains toxic compounds that can cause death of test animals in a certain concentration variation stated in LC50. In this study using freshwater test animals in the form of daphnia magna, daphnia magna is an organism that is sensitive to environmental changes so that it can be determined the concentration of wastewater that can cause toxic effects. The research is an experimental study on a laboratory scale. The research was conducted with a preliminary test and a basic test. LC50 analysis was assessed by the probit method. From the calculation of the probit method, the LC50 value is 67.88% and the TUA (Toxicity Unit Area) value is 1.47, which means that rubber wastewater is very toxic.